Inter-Municipal Cooperation in Latin America: Current Situation and Future Research Challenges [Cooperação Inter-Municipal Na América Latina: Estado Da Arte E Desafios Futuros Da Pesquisa] [Cooperación Inter-Municipal en América Latina: Estado del Arte y Desafíos Futuros de la Investigación] - Arias-Yurisch, K; Retamal-Soto, K; Ramos-Fuenzalida, C (Fundacao Getulio Vargas, 2019)
This article offers an overview of Latin American research on inter-municipal cooperation, a phenomenon that has gained empirical relevance in the region since the 1990s. Based on a systematic literature review and content analysis of 47 articles published between 2005 and 2016 selected from indexed journals (WOS, Scopus, and LatinIndex), this article reports the progress of research, the complexities of the operation, and the different effects of inter-municipal cooperation in Latin American countries. The results identify the main gaps in studies about causes and determinants of ’collaboration’ as an organizational model and territorial governance, as well as the lack of studies on the effectiveness of these arrangements. By identifying these gaps it is possible to guide the future research agenda on cooperation between municipalities. © 2019, Fundacao Getulio Vargas. All rights reserved.